Proposing comprehensive security solutions for IoT networks by improving and integrating methods: DTLS, Quark encryption and Overhearing mechanism - Nguyen, Van Tanh; Ngo, Quang Tri; Nguyen, Linh Giang; Nguyen, Ngoc Cuong; Tran, Xuan Ban (Smart Systems and Devices, 2022)
With the rise of the Internet of Things (IoT), the risk of information security is increasing. There have been many proposals for IoT security, however, so far, there is no truly effective and comprehensive solution. The study aims at lightweight encryption, with the basic goal of reducing the loops of encryption algorithms, reducing the computing requirements, and energy consumption of the system while ensuring safety, and integrating into new Protocols of IoT networks and weak resource devices. Within the framework of this article, we introduce the research results and continue to propose security solutions for IoT networks by improving and integrating DTLS protocols, Quark hash function and Overhearing mechanism, installation, and testing on IoT network structure components, It shows the feasibility and effectiveness of the solution.